Serum Soluble ST2 and IL–33 Levels in Finnish Patients With Juvenile Idiopathic Arthritis - Teräsjärvi, Johanna; Möttönen, Milja; Rahikkala, Heidi; Kvist, Sonja; Anabe, Denise; Mertsola, Jussi; He, Qiushui (John Wiley & Sons, 2026)
In this study, we aimed to investigate whether the levels of serum soluble stimulation 2 (sST2) and interleukin (IL) –33 correlate with Juvenile Idiopathic Arthritis (JIA) subtypes and disease activity, and whether there are differences between sexes. Ninety-four patients under 16 years of age who fulfilled the International League of Associations for Rheumatology (ILAR) classification criteria for JIA were recruited. The control samples included baseline sera collected from healthy Finnish children participating in a vaccine study conducted in Turku, Finland. Serum sST2 and IL–33 levels were measured using ELISA, and the detailed clinical data/parameters were compared. No significant difference was found in serum sST2 levels between male and female controls. A higher level of serum sST2 was observed in male patients with oligoarthritis (median: 33,000 pg/mL) compared to male controls (median 21,600 pg/mL) (p = 0.03), whereas no such difference was found between female patients and controls. Further, a positive correlation between age and sST2 levels was observed in male patients. Notably, no significant correlation was found between serum sST2 or IL–33 levels and disease activity parameters or therapy used. Our findings provide valuable insights in the sex/gender-specific role of sST2 in nonsystemic JIA and warrant further studies of sST2 in children with oligoarthritis in different populations.